Regulation of distinct branches of the non-canonical Wnt-signaling network in Xenopus dorsal marginal zone explants. Issue 1 (December 2016) - Wallkamm, Veronika; Rahm, Karolin; Schmoll, Jana; Kaufmann, Lilian; Brinkmann, Eva; Schunk, Jessica; Kraft, Bianca; Wedlich, Doris; Gradl, Dietmar
Abstract Background A tight regulation of the Wnt-signaling network, activated by 19 Wnt molecules and numerous receptors and co-receptors, is required for the establishment of a complex organism. Different branches of this Wnt-signaling network, including the canonical Wnt/β-catenin and the non-canonical Wnt/PCP, Wnt/Ror2 and Wnt/Ca2+ pathways, are assigned to distinct developmental processes and are triggered by certain ligand/receptor complexes. The Wnt-signaling molecules are closely related and it is still on debate whether the information for activating a specific branch is encoded by specific sequence motifs within a particular Wnt protein. The model organismXenopus offers tools to distinguish between Wnt-signaling molecules activating distinct branches of the network. Results We created chimeric Wnt8a/Wnt11 molecules and could demonstrate that the C-terminal part (containing the BS2) of Wnt8a is responsible for secondary axis formation. Chimeric Wnt11/Wnt5a molecules revealed that the N-terminus with the elements PS3-1 and PS3-2 defines Wnt11 specificity, while elements PS3-1, PS3-2 and PS3-3 are required for Wnt5a specificity. Furthermore, we usedXenopus dorsal marginal zone explants to identify non-canonical Wnt target genes regulated by the Wnt5a branch and the Wnt11 branch. We found thatpbk was specifically regulated by Wnt5a andrab11fip5 by Wnt11. Overexpression of these target genes phenocopied the overexpression of their regulators, confirming the distinct roles of Wnt11 and Wnt5a triggered signaling pathways. Furthermore, knock-down ofpbk was able to restore convergent extension movements in Wnt5a morphants. Conclusions The N-terminal part of non-canonical Wnt proteins decides whether the Wnt5a or the Wnt11 branch of the Wnt-signaling network gets activated. The different non-canonical Wnt branches not only regulate cellular behavior, but, surprisingly, also regulate the expression of different target genes. One of these target genes, pbk, seems to be the relevant target gene executing Wnt5a-mediated regulation of convergent extension movements.